Engaging Farmers and Experts in Feedback loops - the 5Q approach - International Center for Tropical Agriculture (2015)
An overview of CIAT’s pioneering new approach to increase the impact of research projects. 5Q is a simple, cheap and potentially highly-effective monitoring and evaluation system that has been tested in Tanzania.